Brand ambassador, Distribusi, dan Sertifikasi Halal dalam Membangun Ekuitas Merek dan Keputusan Pembelian Kosmetik - Darmawan, Didit; Mochammad Gilang Ramadhan (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
. This literature study aims to analyze the contribution of brand ambassadors to brand equity through the meaning transfer process from public figures to cosmetic products and the reinforcing role of distribution and halal certification in purchase decisions. The method used is qualitative library research with a thematic synthesis approach following systematic literature review procedures. The results indicate that brand ambassadors contribute to brand equity through a three-stage meaning transfer process: meaning formation in the figure, meaning transfer to the product, and meaning acceptance by consumers. The success of meaning transfer is determined by the congruence between figure and brand, ambassador credibility, and communication consistency. Built brand equity encompasses increased awareness, positive associations, perceived quality, and consumer loyalty. Distribution reinforces ambassador influence by ensuring product availability across various channels, facilitating consumers to realize purchase intentions. Halal certification provides legitimacy and security guarantees for Muslim consumers, increasing brand trust. These three factors interact synergistically. Ambassadors build desire, distribution facilitates realization, and certification provides legitimacy. Their integration creates a solid foundation for purchase decisions and long-term loyalty. This study contributes theoretically to enriching meaning transfer models by integrating structural distribution factors and religiosity through halal certification.